ANALISIS PELAKSANAAN KURIKULUM MA PLUS KETRAMPILAN DI MA NEGERI 1 KARANGANYAR - Atun Sakurina , Imro (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
The curriculum is the spirit of educational institutions. 4 curriculum components, namely objectives, material/content, teaching and learning process and evaluation. The implementation of the madrasa curriculum is adjusted to the characteristics of the madrasa. This study aims to determine; Implementation of the 2013 MA Plus Skills Curriculum and Curriculum Components at MAN 1 Karanganyar. This study used a qualitative approach with case study design. The research location is MAN 1 Karanganyar. Research data were collected through observation, in-depth interviews and documentation. Data analysis was carried out with the following procedures: collecting data, reducing, presenting, and verifying data. The results of the study show: (1) It is a research-based madrasa and plus skills, (2) the curriculum implemented is the 2013 curriculum (3) Organizes regular science/IPS/religious classes and skills classes (welding techniques, fashion, machining techniques, motorcycle banking and business techniques, modeling techniques and building information and multimedia);(4) Curriculum implementation focuses on preparing superior, intelligent, skilled, independent, noble and global-minded people (5) Evaluations are carried out regularly to measure the achievement of goals curriculum.